Upaya Peningkatan Kreativitas Anak Usia Dini melalui Kegiatan Menggambar dan Mewarnai Tote Bag di Dusun Ngadirejo Wetan, Desa Pondok, Kecamatan Ngadirojo, Kabupaten Wonogiri - Ferry Rachmanto; Erina Prasdila Ashari; Faris Achmad Baharudin; Himawan Adi Nugroho; Adinda Rusdiani Putri; Asri Wulandari; Hasna Nur Faramida; Hanifah Salsabilla; Putri Oktafia Niawati; Tiara Dyah Puspitasari; Mujiyo Mujiyo (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2022)
Childhood is the most important period because it is the formation of the personality foundation that determines the next child's experience. Creativity can increase productivity, quality of life and the ability to solve a problem. Creativity is very important because it is a superior characteristic of healthy, innovative and productive children's growth. This tote bag drawing and coloring activity aim to increase children's creativity during the pandemic in Ngadirejo Wetan Hamlet, Pondok Village, Ngadirojo Sub-District, Wonogiri Regency. Children's creativity activities are carried out through the demonstration method. This activity was attended by 30 children aged 2 to 6 years in Ngadirejo Wetan Hamlet, Pondok Village, Ngadirojo Sub-District, Wonogiri Regency. The number of participants exceeded the target of the KKN UNS 306 team which was originally only 20 children. The activity was guided and carried out by KKN UNS 306 team with a cheerful atmosphere to increase children's enthusiasm. Stimulus to improve communication skills is also given to children. Evaluations conducted by interviewing parents showed that children's ability to recognize colors was better than before.